Recent Developments in Nanofibers Research (IntechOpen, 2023)
This book presents an overview of the current status and recent trends in nanofibers, their fabrication and applications. The aim is to provide readers with a clear understanding of the electrospinning process both in theory and applications. Challenges, opportunities and new directions for the future development of electrospinning technology are also discussed. The book provides fundamental knowledge and up-to-date information to enable advanced study in the field of nanofibers and their applications. It will therefore be of interest to research students, scientists, engineers, and materials scientists.